2009
DOI: 10.1038/sj.bjc.6605377
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine, oxaliplatin and 5-FU in advanced bile duct and gallbladder carcinoma: two parallel, multicentre phase-II trials

Abstract: BACKGROUND: Gemcitabine, oxaliplatin and 5-fluorouracil (5-FU) are active in biliary tract cancer and have a potentially synergistic mode of action and non-overlapping toxicity. The objective of these trials was to determine response, survival and toxicity separately in patients with bile duct cancer (BDC) and gallbladder cancer (GBC) treated with gemcitabine/oxaliplatin/5-FU chemotherapy. METHODS: Eligible patients with histologically proven, advanced or metastatic BDC (n ¼ 37) or GBC (n ¼ 35) were treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 32 publications
4
33
1
1
Order By: Relevance
“…27 Chemotherapy alone using novel anticancer drugs did not show an acceptable survival period (the median overall survival was 4.7-15.4 months), and the tumor response rate was 9-37% (median progression free survival was 3-7.2 months). [28][29][30][31][32][33][34][35] In Japan, gemcitabine has been mainly used to treat bile duct carcinoma and is now a key drug in the treatment of bile duct carcinoma. 36,37 Previous our studies using cultured cells showed that the main effect of PDT is apoptosis, evidenced by assays that measured either DNA fragmentation or chromatin condensation.…”
Section: Discussionmentioning
confidence: 99%
“…27 Chemotherapy alone using novel anticancer drugs did not show an acceptable survival period (the median overall survival was 4.7-15.4 months), and the tumor response rate was 9-37% (median progression free survival was 3-7.2 months). [28][29][30][31][32][33][34][35] In Japan, gemcitabine has been mainly used to treat bile duct carcinoma and is now a key drug in the treatment of bile duct carcinoma. 36,37 Previous our studies using cultured cells showed that the main effect of PDT is apoptosis, evidenced by assays that measured either DNA fragmentation or chromatin condensation.…”
Section: Discussionmentioning
confidence: 99%
“…(8,(14)(15)(16)(17) Another stratification factor used in this study was the clinical stage (II or III versus IV or recurrent). Locally advanced or metastatic cancer, the stratification factor used in the ABC-01 and ABC-02 studies, (7,18) has been shown to affect the OS of patients with advanced BTC.…”
Section: Gs S-1 Totalmentioning
confidence: 99%
“…However, no standard chemotherapy regimen for advanced BTC has been established. Several phase II trials with new chemotherapeutic agents, such as gemcitabine (6)(7)(8)(9)(10), capecitabine (11), oxaliplatin (12), or S-1 (13,14) have demonstrated tumor response in ~15-35% of patients treated with single agents, and in 20-40% of patients treated with their combinations (15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Among them, gemcitabine has shown promising activity against advanced BTC, and has been commonly used for patients with unresectable or recurrent BTC in Japan.…”
Section: Introductionmentioning
confidence: 99%